Pembinaan Manajemen Investasi dan Analisa Laporan Keuangan Pada Sekolah Menengah Kejuruan (SMK) Multi High School Batam - Wasiman Wasiman (Universitas Pahlawan Tuanku Tambusai, 2022)
The implementation of the service was carried out at the Multi High School Batam Vocational High School (SMK). The purpose of this service is to provide teachers and students with an understanding of investment management and provide an understanding of how to make an analysis of financial statements so that students and teachers understand how to choose profitable investments. The method used in our service is to make presentations to students for 30 minutes and about 1 hour later, it provides the practice of analyzing financial reports and types of profitable investments to students while still providing assistance. The results of community service are Increasing students' and teachers' understanding of investment management and choosing profitable investments. Increase understanding to students and teachers about making correct financial reports in analyzing reports which in the end the report can provide correct and profitable investment choices.